Social Structure Study of Association The Flying Fish Fishermen in Takalar Regency (Case Study in Bontomarannu Village, South Galesong District - Muhammad Dalvi Mustafa; Andi Adri Arief (JURNAL PERIKANAN DAN KELAUTAN, 2017)
This study aims to determined (1) the form of social structure that occur in groups offlying fish fishermen and (2) the rights and duties between the punggawa and sawi insidethe social structure in flying fish fisher groups at Bontomarannu Village of SouthGalesong District, Takalar. The basic method of this research was descriptive methodwith qualitative approach, while the strategy was a case study. The research wasconducted in the Bontomarannu Villages District of South Galesong as one of the flyingfish fisher group who still use the traditional way. Determination of informants conducted snowball sampling where there were 35 informants were used in this study. The resultsshowed that the shape of the social structure of the punggawa sawi in a group of flyingfish fisher form of domination and legitimacy of the role played by the punggawa beingthe highest position in the social relations. The strength of the social structure betweenthe punggawa and sawi belong to the powerful force that created rights and duties ofeach role and status they have in the flying fish fisher groups. Rights and duties were notonly applicable in the employment relationship alone, but more deeply into the journey oflife both within the coastal communities in the Bontomarannu Village. Keywords : punggawa, sawi, social structure, Takalar